Video imaging measurement of interfacial wave velocity in air-water flow through a horizontal elbow - Al-Wazzan, A.; Than, C.F.; Moghavvemi, M.; Yew, C.W. (2001)
Two-phase flow in pipelines containing elbows represents a common situation in the oil and gas industries. This study deals with the stratified flow regime between the gas and liquid phase through an elbow. It is of interest to study the change in wave characteristics by measuring the wave velocity and wavelength at the inlet and outlet of the elbow. The experiments were performed under concurrent air-water stratified flow in a horizontal transparent polycarbonate pipe of 0.05m diameter and superficial air and water velocities up to 8.97 and 0.0778 m/s respectively. A non-intrusive video imaging technique was applied to capture the waves. For image analysis, a flame by frame direct overlapping method was used to detect for pulsating flow and a pixel shifting method based on the detection of minimum values in the overlap function was used to determine wave velocity and wavelength. Under superficial gas velocity of less than 4.44 m/s, the results suggest a regular pulsating outflow produced by the elbow. At higher gas velocities, more random pulsation was found and the emergence of localized interfacial waves was detected. Wave velocities measured by this technique were found to produce satisfactory agreement with direct measurements.